THE PEDAGOGICAL COORDINATOR AND HIS TASKS FACING DEMOCRATIC MANAGEMENT - da Silva, Alex; Maria da Silva, Aurineia; Edimario dos Santos Souza, José; Tacyelle Santos Gomes, Heloísa; Paula Alves Pereira, Débora; dos Santos Lins, Givaldo; Afonso Alves Geronimo, Manuel; Januário da Silva Araújo, Silvia; Cristina Souza, Maryone; Santos Costa, Roseane (Revista Gênero e Interdisciplinaridade, 2024)
The present work deals with the pedagogical coordinator in democratic school management. Democratic school management originated in the 1970s and 1980s, when the state decentralized its power. It is important that this management occurs, so that the elements involved feel part of the decision-making processes and solutions of problems, exercising democracy in search of the collective benefit. The pedagogical coordinator plays a fundamental role in this type of management, not being a leader or an authority, but an articulating leader, who harmonizes the relationships between school, student, teacher, director, community, parents and others involved, always giving priority to the pedagogical proposal decided by team and the qualification of the learning teaching process.